Benzoselenazolium-based hemicyanine dye for G-Quadruplex detection. (15th August 2022) - Li, Zhang-Chi; Wu, Tian-Ying; Zeng, Shu-Tang; Fang, Lan; Mao, Jun-Xin; Chen, Shuo-Bin; Huang, Zhi-Shu; Chen, Xiu-Cai; Tan, Jia-Heng
Graphical abstract: Highlights: SEMA-1 is the first benzoselenazolium-based hemicyanine for G-quadruplex detection. SEMA-1 has potential to detect nucleolar and mitochondrial G-quadruplexes in cells. Benzoselenazolium-based hemicyanine is a valuable scaffold for probe design. Abstract: Benzothiazolium and benzoxazolium are common groups for the construction of hemicyanine dyes; however, their isosteric analogue benzoselenazolium have rarely been studied. Here, we report the development of the first benzoselenazolium-based hemicyanine dye for the selective detection of G-quadruplexes. This molecule, SEMA-1, was validated as a red-emitting and activatable fluorescent probe whose fluorescence would only be activated in the presence of G-quadruplexes in buffer solution. Consistent with this, SEMA-1 was found to accumulate in nucleoli and could be used to detect the high abundance of nucleolar rDNA and rRNA G-quadruplexes in fixed HeLa cells. On the other hand, due to the retained mitochondrial membrane potential in live HeLa cells, SEMA-1 was captured by mitochondria and had the potential to detect the mitochondrial G-quadruplexes. Collectively, this work demonstrates the value of developing G-quadruplex-specific fluorescent probes from novel benzoselenazolium-based hemicyanine scaffold.